Elucidation of heterogeneous graphene nucleation and growth through Cu surface engineering. (June 2019) - Liang, Tao; Habib, Mohammad Rezwan; Kong, Yuhan; Cai, Yu; Chen, Hongzheng; Fujita, Daisuke; Lin, Cheng-Te; Liu, Yingchun; Yu, Cui; Su, Huanxing; Feng, Zhihong; Xu, Mingsheng
Abstract: Graphene synthesis by chemical vapor deposition (CVD) on Cu foil involves a series of complex interplays between the atmosphere and Cu substrate. The large number of topographical irregularities and impure elements existing in the normal Cu foils inevitably result in heterogeneous graphene nucleation and uncontrolled growth. Thus, resolving the mutual entanglements between topographical irregularity, impure element, and carbon is fundamental for the understanding of graphene nucleation and growth. Here, two kinds of Cu surface features, topographical Cu hills and elemental oxygen, are deliberately introduced and their interaction is studied. The synergistic effects of Cu hills and oxygen on graphene nucleation and growth are further demonstrated. Molecular dynamics simulations are employed over the whole process to explain the experimental phenomena including Cu hill construction, oxygen distribution, and carbon adsorption. This work is crucial in revealing the microscopic mechanisms for graphene nucleation and growth, and can shed light on how to controll graphene synthesis via Cu surface engineering. Graphical abstract: Image 10